A Literature Review on User Interface and User Experience Design: Insights from Aesthetic, Emotional, and Adaptive UI Studies - Ilham Zainuri; Muhammad Hafiz Firmansyah; Pandhu Adi Saputra; Fachrudin Pakaja Fachrudin Pakaja (International Journal of Information Systems and Technology, 2025)
The rapid development of digital technology has made user interface (UI) and user experience (UX) design strategic elements in interactive system development. A number of previous studies have discussed UI/UX from various perspectives, ranging from visual aesthetics, emotional design approaches, to the application of adaptive interfaces and personalization on various digital platforms. However, studies that integrate these findings into a comprehensive literature review are still relatively limited. This study aims to examine and synthesize the results of research related to UI/UX design with an emphasis on aesthetic, emotional, and adaptive aspects based on five relevant scientific articles. The research method used is a literature review by analyzing the research objectives, methods applied, and main findings of each study. The results of the study show that visual aesthetic quality has a significant influence on initial perception and user satisfaction levels, while emotion-based design plays a role in increasing user engagement and interaction experience. In addition, the application of adaptive and personalized interfaces has been proven to increase the effectiveness and comfort of use in various application contexts. This study also identified that the user-centered design approach is the dominant framework in UI/UX development. Thus, the results of this literature review are expected to serve as a conceptual reference for researchers and practitioners in designing user interfaces that are more responsive, adaptive, and user-oriented.